Radiation protection value to the operator from augmented reality smart glasses in interventional fluoroscopy procedures using phantoms. Issue 4 (November 2019) - Dorey, S.; Gray, L.; Tootell, A.; Higgins, R.; Al-Islam, S.; Baxter, H.; Dixon, P.; Hogg, P.
Abstract: Introduction: Smart glasses can be adapted to display radiographic images to allow clinician's gaze not to be directionally fixed or predetermined by computer monitor location. This study presents an analysis of eye lens dose during interventional fluoroscopy guided procedures, comparing fixed monitor positions against the use of smart glasses. Methods: Using a head phantom (simulating the clinician), thermoluminescent dosimeters and lead shielded glasses, the dose to the eye was measured for different head 'rotations and tilts' for: gaze directed towards the main scattering source (patient/primary beam) to represent potential gaze direction if smart glasses are used; gaze directed to a range of potential computer monitor positions. An anthropomorphic pelvis phantom was utilised to simulate the patient. Accumulated dose rates (μGy sˉ 1 ) from five 10-second exposures at 75 kV 25.2 mAs were recorded. Results: An average DAP reading of 758.84 cGy cm 2 was measured during each 10 second exposure. Whilst wearing lead shielded glasses a 6.10 – fold reduction in dose rate to the lens is possible (p < 0.05). Influence of the direction of gaze by the clinician demonstrated a wide range of dose rate reduction from 3.13% (p = 0.16) to 143.69% (p < 0.05) when the clinician's gaze was towards the main scattering source. Increased dose rate to the clinician's eyes was received despite wearing lead shielded glasses, as the angle of gaze moved 45° and 90° from 0°. Conclusion: If the clinician's gaze is directed towards the main scattering source a potential exists for reducing eye lens dose compared with fixed location computer monitors. Introduction of lead lined smart glasses into interventional radiology may lead to improvements in patient care, reducing the need for the clinician to look away from the patient to observe a radiographic image. Highlights: An analysis of eye lens dose to the operator during fluoroscopy guided procedures. Dose to the eye of the clinician was measured using thermoluminescent dosimeters. Reduction in eye dose was greatest when the clinician's gaze was towards the patient. Using lead lined smart glasses may improve efficiency and safety for patients. Smart glasses may reduce the need for the clinician to look away from the patient.